Probiotic Mixture Golden Bifido Prevents Neonatal Escherichia coli K1 Translocation via Enhancing Intestinal Defense - Zeng, Qing; He, Xiaolong; Puthiyakunnon, Santhosh; Xiao, Hansen; Gong, Zelong; Boddu, Swapna; Chen, Lecheng; Tian, Huiwen; Huang, Sheng-He; Cao, Hong (Frontiers in Microbiology, 2017)
Escherichia coli (E. coli) K1 sepsis and meningitis is a severe infection characterized by high mortality in neonates. Successful colonization and translocation across the intestinal mucosa have been regarded as the critical steps for E. coli K1 sepsis and meningitis. We recently reported that the probiotic mixture, Golden Bifido (containing live Lactobacillus bulgaricus, Bifidobacterium and Streptococcus thermophilus, LBS) has a preventive role against neonatal E. coli K1 bacteremia and meningitis. However, the interaction between the neonatal gut barrier, probiotics and E. coli K1 is still not elucidated. The present study aims to investigate how LBS exerts its protective effects on neonatal gut barrier during E. coli K1 infection. The beneficial effects of LBS were explored in vitro and in vivo using human colon carcinoma cell lines HT-29 and rat model of neonatal E. coli K1 infection respectively. Our results showed that stimulation with E. coli K1 was able to cause intestinal barrier dysfunction, which were reflected by E. coli K1-induced intestinal damage and apoptosis of intestinal epithelial cells, reduction of mucin, immunoglobulin A (IgA) and tight junction proteins expression, as well as increase in intestinal permeability, all these changes facilitate E. coli K1 intestinal translocation. However, these changes were alleviated when HT-29 cells were treated with LBS before E. coli K1 infection. Furthermore, we found that LBS-treated neonatal rats (without E. coli K1 infection) have showed higher production of mucin, ZO-1, IgA, Ki67 in intestinal mucosa as well as lower intestinal permeability than that of non-treated rats, indicating that LBS could accelerate the development of neonatal intestinal defense. Taken together, our results suggest that enhancement of the neonatal intestinal defense to fight against E. coli K1 translocation could be the potential mechanism to elucidate how LBS confers a protective effect against neonatal E. coli K1 bacteremia and meningitis. This indirect mechanism makes LBS exert preventive effect on most of gut-derived pathogenic infections rather than only E. coli.